Speciation Success of Polyploid Plants Closely Relates to the Regulation of Meiotic Recombination - Pelé, Alexandre; Rousseau-Gueutin, Mathieu; Chèvre, Anne-Marie (Frontiers in Plant Science, 2018)
Polyploidization is a widespread phenomenon, especially in flowering plants that have all undergone at least one event of whole genome duplication during their evolutionary history. Consequently, a large range of plants, including many of the world’s crops, combines more than two sets of chromosomes originating from the same (autopolyploids) or related species (allopolyploids). Depending on the polyploid formation pathway, different patterns of recombination will be promoted, conditioning the level of heterozygosity. A polyploid population harboring a high level of heterozygosity will produce more genetically diverse progenies. Some of these individuals may show a better adaptability to different ecological niches, increasing their chance for successful establishment through natural selection. Another condition for young polyploids to survive corresponds to the formation of well-balanced gametes, assuring a sufficient level of fertility. In this review, we discuss the consequences of polyploid formation pathways, meiotic behavior and recombination regulation on the speciation success and maintenance of polyploid species.